Respon Guru Terhadap Kebijakan Kemenag Tegal Tentang Hafalan Kitab Arbain Nawawi di MTs NU Wahid Hasyim Talang - Eka Nur Fitriyani; Ferri Hidayat; Ikfina Birki Amelia; Laeni Royyani (La-Tahzan: Jurnal Pendidikan Islam, 2023)
The memorization program of Hadith Arba'in Nawawi is one form of implementation of the independent curriculum in madrasas in Tegal Regency. The Independent Curriculum is a practical curriculum from the previous curricula. By implementing this curriculum, students will be taught to memorize hadith and the Quran. The type of research used in this study is qualitative using field qualitative, because what is studied is in accordance with what is in the field directly. The results of this study indicate that the teacher's response to the tegal kemenag policy regarding memorizing hadith arbain nawawi is very responsive and is a new innovation in the implementation of learning, educators strongly support this kemenag program which was implemented after the pandemic. By providing students with a handbook of the hadith arbain nawawi book. In implementing the learning, the head of MTs Nu Wahid Hasyim Talang appointed one of the educators to teach the subject of memorizing hadith arbain nawawi which is included in the local content of reading and writing the Qur'an (BTQ). With the hope that after students have graduated from school they can memorize, understand the meaning, meaning of hadith and can be applied in social life.